2003
DOI: 10.1051/0004-6361:20030440
|View full text |Cite
|
Sign up to set email alerts
|

Unidentified infrared bands in the interstellar medium across the Galaxy

Abstract: Abstract. We present a set of 6-12 µm ISOPHOT-S spectra of the general interstellar medium of the Milky Way. This part of the spectrum is dominated by a series of strong, wide emission features commonly called the Unidentified Infrared Bands. The sampled area covers the inner Milky Way from l = −60• to +60• with a ten-degree step in longitude and nominal latitudes b = 0 • , ±1• . For each grid position the actual observed direction was selected from IRAS 100 µm maps to minimize contamination by point sources a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 28 publications
2
45
1
1
Order By: Relevance
“…Simpson et al (1998);6 : Roelfsema et al (1996); 7 : Verstraete et al (1996); 8 : Henning et al (1998);9 : Moutou et al (1999a); 10 : Moutou et al (1999b);11 : Gerakines et al (1999);12 : Lutz et al (1996) 13 : Lutz et al (1999) 14 : Boulanger et al (1996 15 : Kahanpää et al (2003);16 : Reach et al (2000); 17 : Onaka et al (1996); 18 : Vermeij et al (2002);19 : Werner et al (1976);20 : Thronson et al (1984); 21 : Meixner et al (1992);22 : Casey (1991);23 : Steiman-Cameron et al (1997);24 : Thronson & Harper (1979) …”
Section: Galactic Sampleunclassified
“…Simpson et al (1998);6 : Roelfsema et al (1996); 7 : Verstraete et al (1996); 8 : Henning et al (1998);9 : Moutou et al (1999a); 10 : Moutou et al (1999b);11 : Gerakines et al (1999);12 : Lutz et al (1996) 13 : Lutz et al (1999) 14 : Boulanger et al (1996 15 : Kahanpää et al (2003);16 : Reach et al (2000); 17 : Onaka et al (1996); 18 : Vermeij et al (2002);19 : Werner et al (1976);20 : Thronson et al (1984); 21 : Meixner et al (1992);22 : Casey (1991);23 : Steiman-Cameron et al (1997);24 : Thronson & Harper (1979) …”
Section: Galactic Sampleunclassified
“…The fact that the bands are detected far from any illuminating source with roughly the same intensity ratios as those close to bright stars proves that the carriers are excited nonthermally by single UV photons (Sellgren 1984) and are interstellar. Indeed, both CAM-CVF and PHOT-S as well as the IRTS have shown that the mid-IR spectra (and thus also the IRAS 12 µm emission) of even the most diffuse interstellar medium are dominated by PAH features (Mattila et al 1996, Onaka et al 1996, Boulanger et al 2000, Kahanpää et al 2003. Any large (>100Å) grain does not become hot enough under these conditions to emit at mid-IR wavelengths, so the carriers must be small, of order 10Å, and correspond to PAHs with 30 to a few hundred carbon atoms containing up to 10-15% of the available interstellar carbon.…”
Section: Polycyclic Aromatic Hydrocarbonsmentioning
confidence: 99%
“…The origin of the difference between class A and B objects may be attributed to the inclusion of hetero atoms (Peeters et al 2002) or carbon isotopes in the band carriers (Wada et al 2003). On the other hand, the UIR band spectrum observed in the diffuse Galactic radiation does not exhibit any systematic variations in the inner part of the Galaxy (Chan et al 2001;Kahanpää et al 2003), whereas Sakon et al (2004) detected small variations in the band ratio and the peak wavelength between the inner part of the Galaxy and the outer part. Variations in the band spectra of external galaxies and within a given galaxy are also generally small (e.g., Smith et al 2007a;Gordon et al 2008).…”
Section: Introductionmentioning
confidence: 90%